MODERN APPROACHES TO DEVELOPING STUDENTS’ CREATIVITY IN THE DISTANCE EDUCATION SYSTEM - Rasulova Zilola Durdimurotovna,Bekhnazarova Dilafruz Amirovna (International Journal of Literature and Language Studies, 2026)
The article highlights the organization of the distance education system in higher education and the essence of transforming the Internet system and information technologies into a means of acquiring, storing, transmitting new knowledge, as well as making practical decisions within the educational process. The possibilities of the purposeful use of distance education are also revealed.